(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This research is motivated by the importance of preserving Tari Silek Kain as one of the traditional arts that developed in Nagari Taluak Kualo, Kecamatan Airpura, Kabupaten Pesisir Selatan. The existence of this dance needs to be maintained so that it remains recognized and passed down to the younger generation. The results show that the preservation efforts for Tari Silek Kain are carried out through cultivation, development, quality improvement, and quantity increase of the dancers. Cultivation is conducted through routine practices and the transmission of dance to the younger generation. Development is achieved by adapting the dance presentation without diminishing its traditional values. Quality improvement is carried out through movement technique learning and evaluation of the dancers’ abilities, while quantity increase is achieved through the recruitment of new members and the involvement of the younger generation in the studio’s activities. These efforts demonstrate that Sanggar Seni Puti Gubalo Intan plays an essential role in maintaining the sustainability of Tari Silek Kain as a cultural heritage of the society in Nagari Taluak Kualo.